(untitled) (مجلة العلوم الشاملة, 2025)
Arabic :is characterized by iʿrāb (inflection), a key feature essential to understanding its grammar. Changing inflection can alter meaning, and due to similarities between grammatical roles and word structures, confusion often arises. Although grammar books aim to clarify this, muʿribs still face difficulties. To ensure clarity and avoid ambiguity, grammarians established strict rules for iʿrāb